A novel route to 4, 4′-disubstituted bipyridyl ligands in ruthenium complexes for dye-sensitized solar cells. (29th March 2015) - Odling, Gylen; Chadwick, Nina; Frost-Pennington, Ewan; Kumar, D. Kishore; Ivaturi, Aruna; Upadhyaya, Hari M.; Robertson, Neil
Graphical abstract: In situ nucleophilic aromatic substitution provides a simple route to functionalization at the 4, 4′ positions of bipyridyl units co-ordinated to a Ru(II) centre. The resulting new Ru(II) sensitiser [RuII(4, 4′-dicarboxy-2, 2′-bipyridyl)(4, 4′-dithiocyanate-2, 2′-bipyridyl)dithiocyanate] is studied in dye-sensitised solar cells. Abstract: An in situ nucleophilic aromatic substitution reaction has been observed and applied as a simple route to introduce functionality to the 4, 4′ positions of bipyridyl units coordinated to a Ru(II) centre. This has been used in the synthesis of a new Ru(II) sensitiser complex [Ru II (4, 4′-dicarboxy-2, 2′-bipyridyl)(4, 4′-dithiocyanate-2, 2′-bipyridyl)dithiocyanate]1 for use in dye-sensitised solar cells.1 exhibits improved light harvesting in the 350–450 nm region in comparison with N719 and produced cells with power conversion efficiencies of 3.18%.